2020
DOI: 10.21203/rs.3.rs-59456/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulated Bile Acid Receptor-mediated Signaling and IL-17A Induction are Implicated in Diet-associated Hepatic Health and Cognitive Function

Abstract: Background: Chronic consumption of high sugar and high fat diet associated with liver inflammation and cognitive decline. This paper tests a hypothesis that the development and resolution of diet-induced nonalcoholic fatty liver disease (NAFLD) has an impact on neuroplasticity and cognition. Methods: C57BL/6 wild-type mice were fed with either a healthy control diet (CD) or a fructose, palmitate, and cholesterol (FPC)-enriched diet since weaning. When mice were 3-months old, FPC diet-fed mice were randomly ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For example, Bifidobacterium was known to produce the acetate that can protect against enteric infection in mice (Rabbani et al, 1999;Fukuda et al, 2011;Sepuĺveda et al, 2018); Bacteroides was also the main bacteria involved in producing SCFA and play an important role (Kaakoush et al, 2014;Comstock, 2009). Lactobacillus produced butyrate by altering the intestinal microbiota, which maintains homeostasis in the gut, reduces inflammatory responses and serves as a source of energy for the renewal of intestinal epithelial cells (Jhun et al, 2021;Tian et al, 2019;Jena et al, 2020). As shown in Figure S6, it was found that SCFA-producing genera in the donor, such as Bifidobacterium and Bacteroides that colonized mice, may play a key role in the treatment of UC mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bifidobacterium was known to produce the acetate that can protect against enteric infection in mice (Rabbani et al, 1999;Fukuda et al, 2011;Sepuĺveda et al, 2018); Bacteroides was also the main bacteria involved in producing SCFA and play an important role (Kaakoush et al, 2014;Comstock, 2009). Lactobacillus produced butyrate by altering the intestinal microbiota, which maintains homeostasis in the gut, reduces inflammatory responses and serves as a source of energy for the renewal of intestinal epithelial cells (Jhun et al, 2021;Tian et al, 2019;Jena et al, 2020). As shown in Figure S6, it was found that SCFA-producing genera in the donor, such as Bifidobacterium and Bacteroides that colonized mice, may play a key role in the treatment of UC mice.…”
Section: Discussionmentioning
confidence: 99%